Testing the validity of a stage assessment on health enhancing physical activity in a chinese university student sample - Yanping Duan; Sonia Lippke; Ru Zhang; Walter Brehm; Pak-Kwong Chung (BMC, 2016)
Abstract Background The study examined the measurement quality of a stage algorithm measuring the Four steps from Inactivity to activity Theory (FIT Model). Methods In a cross-sectional study, stages were assessed in 1012 Chinese university students in terms of physical activity, social-cognitive variables and health outcomes. Main outcome measures were stages of change, self-reported physical activity, perceived barriers, intrinsic motivation, plans, fitness and health satisfaction. Misclassification, sensitivity, specificity, receiver operating characteristic (ROC) curves, nonlinear trends, and planned comparison were computed. Results Compared to previous studies, sensitivity was at the average level (64 %-71 %), and specificity was comparably higher (76%-89%). When using higher PA intensity criteria (moderate and strenuous intensities), sensitivity was higher, whereas specificity was lower in comparison to the lower PA intensity criteria (also including mild activity). After running contrast and trend analyses, nonlinear trends for all indicative variables across the stages and a match of 77 % of predictions of stage differences were confirmed. Conclusion The measurement quality of the stage algorithm was supported in a young adult sample.